On the Rhetorical Strategies of Psychological Discourse in E-Counselling Response to Lovelorn College Students - Haoran, Mao; Fang, Zhang (Sinología hispánica. China Studies Review, 2016)
This paper analyses the advantages and rhetorical strategies of psychological E-Counselling discourse, based on successful cases in response to lovelorn college students. It is found that: (1) Psychological E-Counselling discourse of college students can be divided into time-lapse discourse via email and impromptu online discourse via QQ. Remote communication via the internet, privacy by anonymity, and trust in teachers as consultants are the three main reasons for the increasing number of lovelorn college students asking their teachers for psychological E-Counselling, which has advantages compared to traditional face-to-face counselling, and also broad application prospects; (2) The rhetorical strategies of psychological E-Counselling discourse in response to lovelorn college students include: setting interlocking leading questions to understand the psychological distress of students, employing appropriate rhetorical questions straight to the point to cut off negative turns of dialogues, establishing proper psychological frames of reference to undermine the negative self-judgement of students, citing topic-related words, phrases and stories which are with philosophical ideas or popular at the time to strike a chord with students, providing concrete suggestions to reactivating students, and making use of group discourse at interactive platforms as an additional strategy.